2021
DOI: 10.1111/febs.16078
|View full text |Cite
|
Sign up to set email alerts
|

Cutting into wound repair

Abstract: The skin is home to an assortment of fibroblastic lineages that shape the wound repair response toward scars or regeneration. In this review, we discuss the distinct embryonic origins, anatomic locations, and functions of fibroblastic lineages, and how these distinct lineages of fibroblasts dictate the skin's wound response across injury depths, anatomic locations, and embryonic development to promote either scarring or regeneration. We highlight the supportive role of the fascia in dictating scarring outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 122 publications
0
18
0
Order By: Relevance
“…Furthermore, studies by Harris and colleagues showed that the traction force of individual fibroblasts in wounds was significantly more than the force needed for cell movement and hypothesized that the extra force was used for dragging matrix fibers [45]. The recent findings of the pivotal role for subcutaneous fascia support these earlier findings [29,46].…”
Section: Wound Repair By Subcutaneous Fasciamentioning
confidence: 88%
See 2 more Smart Citations
“…Furthermore, studies by Harris and colleagues showed that the traction force of individual fibroblasts in wounds was significantly more than the force needed for cell movement and hypothesized that the extra force was used for dragging matrix fibers [45]. The recent findings of the pivotal role for subcutaneous fascia support these earlier findings [29,46].…”
Section: Wound Repair By Subcutaneous Fasciamentioning
confidence: 88%
“…Superficial fascia is constantly thicker in women compared to men at various anatomical sites. For instance, female subcutaneous fascia at back is 15% thicker than male (0.16 mm vs. 0.14 mm) [13], while back skin in women is 55% thinner than in men (1.5 mm vs. 2.3 mm) [46]. The combination thicker subcutaneous fascia and thinner skin implies that injury of female skin more easily breaches the fascial compartment.…”
Section: Fibrotic Outcomes Of Fascia Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Spiny mice are notable for their ability to regenerate skin through wound‐induced hair neogenesis (WIHN). WIHN does occur in the house mouse, but only in severe wounds and to a much lesser extent 26–34 . During WIHN, a progeny of interfollicular, epidermal and dermal cells become ‘embryonic‐like’ to restore early epithelial‐mesenchymal interactions, resulting in the regeneration of hair follicles, fat and arrector pili muscle 35 .…”
Section: Introductionmentioning
confidence: 99%
“…or reflect underlying functional/positional differences. [3][4][5][6] It is thus of utmost importance that the scientific community interested in a specific tissue or cell type agrees on the existing subsets within particular cell types and their defining molecular profiles, so that a common reference atlas may be used to understand homeostasis and response to varying insults. 7 In a re-analysis of 13,823 human adult dermal fibroblasts obtained from four independent scRNAseq studies, [8][9][10][11] we recently proposed that human skin presents a common set of fibroblast subsets, irrespective of donor area.…”
Section: Introductionmentioning
confidence: 99%